Leadership Styles of Female Principals in the Context of Educational Management at MTs in Sukabumi Regency: A Multi-Case Study - Arfiani Yulianti Fiyul (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study presents the findings of a qualitative investigation that explores the leadership styles of female principals at two madrasah tsanawiyah (MTs) in Sukabumi Regency. Using a multi-site case study approach, the research reveals that the dominant leadership practices are participative and transformational in nature. Female principals demonstrate strong abilities in fostering open communication, prioritizing collaboration, and providing motivation through empathetic and humanistic approaches. The findings also indicate that although the principals successfully cultivate supportive school environments, they continue to face challenges rooted in patriarchal culture and gender stereotypes that limit their authority and decision-making capacity. Data were collected through observation, in-depth interviews, and systematic document analysis. The results show that the leadership roles of female principals are significantly influenced by the local socio-cultural context, including societal perceptions of women in leadership. Nevertheless, their approaches effectively foster harmonious relationships, enhance teacher performance, and create inclusive learning environments. This study contributes empirical insights to the literature on gender-based educational leadership at the madrasah level, particularly within local contexts characterized by strong religious-cultural values. The findings provide a solid foundation for developing policies and training programs that support female leadership in education, and serve as a critical reference in promoting gender equality in school leadership practices.